Evidence of Biocontrol Activity of Bioinoculants Against a Human Pathogen, Listeria monocytogenes - Sharma, Richa; Gal, Laurent; Garmyn, Dominique; Bisaria, V. S.; Sharma, Shilpi; Piveteau, Pascal (Frontiers in Microbiology, 2020)
Due to rhizodeposits and various microbial interactions, the rhizosphere is an extremely dynamic system, which provides a conductive niche not only for bacteria beneficial to plants but also for those that might pose a potential threat to humans. The importance of bioinoculants as biocontrol agents to combat phytopathogens has been widely recognized. However, little information exists with respect to their role in inhibiting human pathogens in the rhizosphere. The present study is an attempt to understand the impact of an established bacterial consortium, Azotobacter chroococcum, Bacillus megaterium, and Pseudomonas fluorescens, on the survivability of Listeria monocytogenes in the rhizosphere of Cajanus cajan, and Festuca arundinacea. An experiment conducted in Hoagland’s medium in the presence of C. cajan demonstrated that the abundance of L. monocytogenes was 14.5-fold lower in the presence of bioinoculants compared to in their absence. On the other hand, in the presence of F. arundinacea, no significant differences were observed in the population dynamics of L. monocytogenes in the presence or absence of bioinoculants. Agar plate assay through cross streak method revealed the inhibition of L. monocytogenes by bioinoculants. Potentialbioactive compounds were identified by ultra-performance liquid chromatography-mass spectrometry (UPLC-MS). These results suggest that agricultural amendments can act as protective agents against human pathogens while enforcing plant growth promotion.